On Brazilian Federal Council of Psychology (CFP) Resolution 001/1999 and the Sexual orientation change efforts (SOCE): Record of a permanent struggle - Zamignani, Denis Roberto; Rocha, Giovana Veloso Munhoz (Perspectivas em Análise do Comportamento, 2022)
This article consists of a historical record of a document prepared on behalf of the Brazilian Association of Behavioral Sciences – ABPMC, motivated by a decision rendered in response to Popular Action nº 1011189-79.2017.4.01.3400. The Action proposedd on August 2017, proposed a reinterpretation of the Resolution of the Federal Council of Psychology CFP No. 001/1999 aiming to allow the psychologist to promote scientific studies and professional assistance to sexual reorientation. Still in the same year the Federal Judge of the 14th Court of the Federal District, Waldemar Cláudio de Carvalho, granted an injunction in favor of Popular Action, mobilizing a portion of the scientific community, especially in psychology and in institutions linked to the causes of defense of Human Rights, against the Action. The document fully reproduced here consisted of a motion of repudiation, published by the ABPMC, recaptures the principles that support the CFP Resolution, as well as the determinations of the American Psychiatric Association in 1973 and the World Health Organization (WHO) in 1990, which removed homosexuality from the list of diseases. It also points out the mistake of appealing to scientific freedom to arbitrate over a psychological practice, placing under the same scrutiny practices of different categories that respond to different principles and criteria. Finally, it collects data that demonstrate the ineffectiveness and harmful nature of so-called sexual reorientation therapies.